2014
DOI: 10.1507/endocrj.ej13-0403
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis and growth activity depend on patient age in clinical and subclinical papillary thyroid carcinoma [Review]

Abstract: Abstract. In this review, we focused on the patient age as an indicator of tumor growth and prognostic significance in both clinical papillary thyroid carcinoma (PTC) and subclinical papillary microcarcinoma (PMC: PTC ≤ 1 cm). In clinical PTC, young age (< 30 years) and old age (≥ 60 years) significantly affected the disease-free survival of patients, and old age was a strong predictor of carcinoma death. In contrast, in subclinical PMC, growth activity significantly decreased with patient age, and young age (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 60 publications
1
28
0
7
Order By: Relevance
“…Ito et al performed a multivariate analysis and found that not only old age (≥ 60 yrs) but also young age (< 30 yrs) were independent predictors of locoregional and distant recurrence of PTC [13]. Ito and Miyauchi et al also demonstrated that papillary microcarcinoma (PMC: PTC ≤ 1 cm) in young patients (≤ 40 yrs) is more likely to progress during observation [14,15]. These findings suggest that the developing activity of PTC in young patients is high, although their CSS is excellent.…”
Section: D) Extrathyroid Extension (Ex)mentioning
confidence: 99%
“…Ito et al performed a multivariate analysis and found that not only old age (≥ 60 yrs) but also young age (< 30 yrs) were independent predictors of locoregional and distant recurrence of PTC [13]. Ito and Miyauchi et al also demonstrated that papillary microcarcinoma (PMC: PTC ≤ 1 cm) in young patients (≤ 40 yrs) is more likely to progress during observation [14,15]. These findings suggest that the developing activity of PTC in young patients is high, although their CSS is excellent.…”
Section: D) Extrathyroid Extension (Ex)mentioning
confidence: 99%
“…[3][4][5]. However, some investigators reported that advanced age might represent a risk factor for more aggressive and/or more rapidly progressive RCC [6].…”
Section: Introductionmentioning
confidence: 99%
“…Young patients (<40 years) were more likely to experience thyroid tumor enlargement and novel lymph node appearance compared with middle-age (40-59 years) and older patients (>60 years) (15,16). An increase in the size of the PMC was seen in four of the nine women who became pregnant while being followed with active surveillance (14).…”
mentioning
confidence: 97%